First record of the Lycian Bright Bush-Cricket Poecilimon inflatus lyciae (Orthoptera: Tettigoniidae) in Greece - Kazilas, Christos; Kalaentzis, Konstantinos; Drakopoulos, Panagiotis; Willemse, Luc (ENTOMOLOGIA HELLENICA, 2023)
The genus Poecilimon currently includes 145 species of bush crickets distributed in the Palearctic. A great number of representatives within this genus is concentrated in the Aegean region and more specifically in Greece. In this short note, we present the first record of the Lycian Bright Bush-Cricket, Poecilimon inflatus lyciae in Greece, observed during a series of zoological expeditions on the island of Kastellorizo (Dodecanese, Greece). This species is the seventh known member of the P. jonicus group and the 46th species of Poecilimon recorded from Greece. This study contributes to the knowledge of the biodiversity of Kastellorizo archipelago, which remains widely understudied.